The Role of Souvenir in Tourism Indonesia: a Thematic Review - Melany; Sudarmiatin (PT FORMOSA CENDEKIA GLOBAL, 2023)
This systematic literature review aims to explore the relationship between souvenir and tourism. The review identified 20 relevant studies published between 2012 and 2023, which were analyzed using a thematic approach. Thematic analysis is a useful method for identifying and analyzing themes and patterns in qualitative data related to souvenirs and tourism. The findings suggest that souvenir serve as important symbols of identity and culture, promoting cultural exchange and understanding between different groups of people, and contributing to the preservation and promotion of local heritage and traditions. And the recommendation for future research could develop more effective strategies for promoting sustainable souvenir consumption practices.